Children Playing Video Games During COVID-19 In Spain - Escudero, Carolina (Advances in Social Sciences Research Journal, 2022)
As has been verified, those who spend more time playing video games are children and adolescents. The lockdown caused by the COVID-19 pandemic increased the prolonged use of video games in this population. In this context it is possible to observe some risks of this use, one of them the symptoms of gaming disorder (GD). The objective of this study is to analyze video game habits and the possible impacts on children - aged between 7 and 10 years – gaming for more than 4 hours daily during confinement - the lockdown was announced on March 14, 2020 and lasted approximately three months.- in Spain. Likewise, this study examines how families have acted after the detection of possible dependencies. According to the (10) families interviewed, the children have modified their routines, changed their mood, their symbolic games and –some of them– developed a clear dependency on the screen(s). Faced with this reality, the majority of the families created various strategies in order to modify these new habits and reduce the exposition to video games; others they decided to contact professionals to receive some assistance with their children’s behavior. The lack of knowledge of families about the use of video games is observed in three specific areas: first, knowing if it is an appropriate game for their child's age; second, set time limits; finally in being able to evaluate the dependency to the game. Based on the results, the study of video games in children requires the development of broader, complex and coherent approaches that focuses on the intra-family experience and parents’ skills to be with their children in this context. In addition, approaches that include spaces for the effective education of families about video games, including workshops and tools represent a clear need that could be addressed from schools or related institutions.